Validation of media interactive learning in vocational high school - Apriyus, Devri Ramdhan; Rukun, Kasman; Huda, Asrul; Marta, Satria Ami (Jurnal Pendidikan Teknologi Kejuruan, 2020)
This research is motivated by the need for the media to learn that promote interaction and understanding of learning. The purpose of this research was: 1) to produce interactive learning media on Basic Graphic Design subjects at vocational high school. 2) Determining the validity of interactive learning media on Basic Graphic Design subjects at vocational high school. The method used is a Research and Development (R & D). The development Model used is 4-D (Four-D). The 4-D consists of four stages, namely discovering, designing, developing and disseminating. The subjects of research conducted were material experts and media experts. The instrument used to measure the form of validity is the questionnaire responses. The validity of interactive learning media is assessed from two aspects namely media feasibility and feasibility aspects of the matter. The results of this research indicate that interactive learning media on Basic Graphic Design subjects is considered valid as seen from the average value of media validation by 0.87 and the average result of 0.85 material validation. Based on the results of the validation of the interactive learning media on Basic Graphic Design subjects are feasible for use in assisting the learning process.